Penentuan Pembukaan Gerai dengan Menggunakan Analytic Hierarchy Process Empat Layer - Muhammad Dzulfikar Fauzi; Granita Hajar; Abdul Kholik (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
In the neighborhood, there is a slew of flavored drink shops. Bubble drinks, sometimes known as "boba drinks," are currently popular across various demographics, particularly among teenagers and young people. The sweet taste of the drink and the range of options drive demand for this boba drink, which is growing increasingly popular. In addition to its presentation, this beverage producer offers customization options for beverage taste, sugar level, drink glass size, and even ice cube quantity to satisfy consumer preferences. Several criteria, such as pricing, purchasing power, and location, must be considered while deciding on store opening These elements can still be subdivided. Therefore the AHP (Analytical Hierarchy Process) method is appropriate for determining store openings. The findings of this study demonstrate that, among numerous alternative locations, location G has the highest value, with a weight of 0.2236.